Prevalence and relationship between falls, frailty phenotype and physical activity in centenarians: a pilot study - Trento M.C.M.* (2023)
© 2023, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.The objective of this study was to associate the occurrence of falls with the frailty phenotype and physical activity (PA) in centenarians. Population-based descriptive study carried out in the state of Santa Catarina, Brazil, which included 54 centenarians (101.8 ± 2.8 years), 34 women and 20 men. To assess PA, centenarians wore a pedometer for 7 days of a typical week. The occurrence of falls was confirmed by self-report and frailty phenotype using the criteria proposed by Fried et al. (2001). All assessments were carried out following the Multidimensional Assessment Protocol for the Centennial Elderly, applied through interviews. The chi-square test with adjusted standardized residuals was used to evaluate the association between the occurrence of falls and frailty and AF, adopting a significance level of 5%. The prevalence of frailty in the sample was 53.7%. The majority of centenarians did not do PA (66.7%) and did not suffer a fall in the last 12 months (68.5%). The average number of weekly steps was higher among fallers (1,796.1 steps/week) when compared to non-fallers (797.4 min/week) (p=0.019). There was a significant association between falls and frailty (p=0.03), with fallers tending to be frail. The occurrence of falls was also associated with AF (p=0.014), with fallers tending to be physically active. Concluding that centenarians with falls in the last 12 months showed a tendency to frailty and a higher level of PA. The results demonstrate the importance of monitoring frailty in this population and of PA interventions that aim to reduce the factors causing this condition.